ChemInform Abstract: Catalyst‐Free Synthesis of (E)‐2‐Alkenylquinoline Derivatives via C(sp3)‐H Functionalization of 2‐Methylquinolines. Issue 18 (May 2015) - Xu, Lubin; Shao, Zhuzhou; Wang, Liang; Zhao, Huaili; Xiao, Jian
Abstract The electronic properties of the aromatic aldehydes do not only influence the reaction yields, but also whether E‐alkenylquinoline derivatives are obtained exclusively or together with hydrated or dimerized products.